MEASURING SCIENCE PROCESS SKILLS: THE IMPLEMENTATION OF TWO-TIER MULTIPLE CHOICE (TTMC) ASSESSMENT INSTRUMENT - Ratnasari, Dewi; Sukarmin, Sukarmin; Suparmi, Suparmi (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
As it has been stressed on within the educational program curriculum, science process skills acquisition is an inextricable outcome of a science learning program. Therefore, the proper type of assessment for measuring science process skills is an inseparable part of science education program. In this study, we use a Two-Tier Multiple Choice (TTMC) assessment instruments to measure 148 senior high schools students’ science process skills. Through TTMC assessment instrument, we found that the students' skills in six different science process skills indicators were varied, with skills to communicate scientific concepts as the highest level of acquisition.